The Pervasiveness of Archives - Gabriella Ivacs (Lea, 2013)
Regardless of the widely spread use in historiography, anthropology, cultural studies, information sciences, archives is a heavily inflated word. Beginning with the ancient Greek administrative role of Archeion, the emergence of archival institution as a symbolic mean to strengthen national identity in the age of nation states, through referencing social construction and parallel stories of postmodern historiography, there is a need for a new archival theory to connect high level theories with new archival practices embedded in the dig- ital society. The essay tries to remove some interpretative layers from the non-discoursive practices of archives and it yields the generative nature of its architecture by referencing media archeology as method. The analysis of Eastern and Central European historical examples add nuance to our understanding of archival complexities: the fate of secret police files in the Post-Communist societies, how to serve the collective memory of traumatized nations with new approaches to collection management, and finally, referencing Pan-European efforts to cooperate or to compete with huge private technology providers in the digital age. The essay is part of a growing body of research on resituating “the archival identity” and suggesting to examine both static and dynamic archives in the light of technology developments to understand digital forgetting, digital remembering and controlling data for the whole society.